Applications and mechanisms of immunotherapy in allergic rhinitis and asthma. (January 2017) - Kappen, Jasper H.; Durham, Stephen R.; Veen, Hans In 't; Shamji, Mohamed H.
Clinical and immunologic tolerance are hallmarks of successful allergen immunotherapy (AIT). Clinical benefits such as reduced symptoms, pharmacotherapy intake and improvement of quality of life persist following cessation of treatment. Successful AIT is associated with suppression of allergic inflammatory cells such as mast cells, eosinophils and basophils in target organs. Furthermore, AIT down-regulates type 2 innate lymphoid cells and allergen-specific type 2 T-helper (Th2) cells. The immunologic tolerant state following AIT is associated with the induction of distinct phenotypes of regulatory T-cells (T-regs) including interleukin (IL)-10-, IL-35- and transforming growth factor (TGF)-β- producing T-regs and FoxP3 + T-regs. B-cell responses, including the induction of IL-10 + regulatory B-cells (B-regs) and the production of IgG4-associated blocking antibodies are also induced following successful AIT. These events are associated with the suppression of antigen-specific Th2 responses and delayed immune deviation in favour of Th1 type responses. Insight into the mechanisms of AIT has allowed identification of novel biomarkers with potential to predict the clinical response to AIT and also novel therapeutic strategies for more effective and safer AIT.